A Review on the Antimutagenic and Anticancer Effects of Cysteamine - Chun-Man Lee (Advances in Pharmacological and Pharmaceutical Sciences)
Cancer is one of the leading causes of death worldwide. First-line treatments usually include surgery, radiotherapy, and/or systemic therapy. These methods can be associated with serious adverse events and can be toxic to healthy cells. Despite the new advances in cancer therapies, there is still a continuous need for safe and effective therapeutic agents. Cysteamine is an aminothiol endogenously synthetized by human cells during the degradation of coenzyme-A. It has been safely used in humans for the treatment of several pathologies including cystinosis and neurodegenerative diseases. Cysteamine has been shown to be a potent antimutagenic, anticarcinogenic, and antimelanoma in various in vitro and in vivo studies, but a review on these aspects of cysteamine’s use in medicine is lacking in the current literature. The efficacy of cysteamine has been shown in vitro and in vivo for the treatment of different types of cancer, such as gastrointestinal cancer, pancreatic cancer, sarcomas, hepatocellular carcinoma, and melanoma, leading to the significant reduction of lesions and/or the increase of survival time. Although the mechanisms of action are not fully understood, possible explanations are (i) free radical scavenging, (ii) alteration of the tumor cell proliferation by affecting nucleic acid and protein synthesis or inhibition of DNA synthesis, and (iii) hormone regulation. In conclusion, regarding the high safety profile of cysteamine and the current literature data presented in this article, cysteamine might be considered as an interesting molecule for the prevention and the treatment of cancer. Further clinical studies should be performed to support these data in humans.